Opini Hukum dan Harmonisasi Undang-Undang Cipta Kerja Di Indonesia - Sarah Qosim (ADALAH, 2022)
The sensitivity of harmonization to the regulation of the Manpower Law into Law No. 11 of 2020 concerning Job Creation (Omnibus law) gave birth to various debates among legal experts in Indonesia. The establishment of the Job Creation Law in Indonesia is considered not based on the methods specified in the 1945 Constitution and Human Rights. This is based on legal considerations that have been read by Constitutional Judge Soehartoyo. Following the joint agreement of the Dpr and the President, many components of the text of the Job Creation Law were changed. This article agrees with the opinion of Edi Kastro (2020), Chamdani (2022) that the role of the government is very much needed in the welfare of human rights as long as it does not conflict with other laws and regulations.